Catalytic Studies Featuring Palladium(II) Benzoylthiourea Derivative as Catalyst in Sonogashira Reaction - Wan M. Khairul; Sarah Liyana Mohd Faisol; Siti Maryam Jasman; Siti Kamilah Che Soh; Mustaffa Shamsuddin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
A benzoylthiourea derivative (LTU) and its metal complexation of palladium(II) chloride (MLTU) has been successfully synthesized and characterized via typical spectroscopic and analytical techniques namely IR, 1H and 13C Nuclear Magnetic Resonance, UV-Visible and Gas Chromatography Flame Ionization Detector (GC-FID). The Infrared spectrum for LTU shows four significant bands of interest namely ν(N-H), ν(C=O), ν(C-N) and ν(C=S) and the values were observed within the range. The 1H NMR spectrum for the compound shows expected protons for N-H at δH 10.95 ppm and δH 11.15 ppm while the 13C NMR spectrum shows resonances of carbonyl (C=O) carbon and thiones (C=S) at δC 168.26 ppm and δC 180.56 ppm, respectively. From UV-Vis spectrum, it shows the presence of n-pi* and pi→pi*electronic transitions which are expected to be attributed from the phenyl ring, carbonyl (C=O) and thiones (C=S) chromophores. Complexation of LTU with palladium(II) chloride was done to afford MLTU which in turn, was tested as homogeneous catalyst in Sonogashira cross-coupling reaction. The reaction was monitored by GC-FID at 6 hours reaction period. The percentage conversion of 4-bromoacetophenone to the coupled product was 75.73% indicated that MLTU can act as an ideal potential catalyst in the Sonogashira reaction. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)